The lost paradise. Foreigners condemned for organized crime in prisons of Spain (2011)
Based on data from an empirical research conducted by the IAIC, Cadiz, with foreigners in Spanish prisons convicted of organized crime, we can conclude that the category “foreigner-criminal-organized crime”, which works in the collective imagination by as